Empowerment and agricultural mechanisation: perceptions and experiences of women tractor operators in Ghana. Issue 8 (17th November 2021) - Cele, Lungelo
ABSTRACT: Development projects play a crucial role in kickstarting and promoting women's empowerment in agriculture. This paper is a conversation starter on how women can be included in the agenda to mechanise agriculture in Africa. It investigates the potential of empowering women as vital actors in the mechanisation value chain, by analysing the perceptions and experiences of the trained women tractor operators. The findings showed that the involvement of women in mechanisation pushed them beyond their comfort zones and offered them a new self-identity with new opportunities previously reserved for men. It also broadened their social capital through the formation of an association for women operators which ensured their representation at a local and national level. For young women, being an operator is the only alternative they have to one day owning a tractor-for-hiring service business because they do not own land or have capital, which is often a precondition.